Anatomy of the sporophyte of Anemia phyllitidis var. phyllitidis (Anemiaceae) from a riparian forest (Tucumán, Argentina) - Albornoz, Patricia Liliana; Romagnoli, María Gabriela; Hernández, Marcela Alicia (Instituto de Ecología, A.C., 2021)
Background and Aims: In Argentina seven species of the genus Anemia are recognized; one of them, A. phyllitidis, has two varieties. The anatomical records for A. phyllitidis var. phyllitidis are scarce and refer to the ontogeny of stomata, epidermis structure and type of petiole stele. This variety, which occurs in riparian forests, is affected by the increase of seasonal ecological pressures. There is scarce information about its sporophyte anatomy; hence, the aim of this work was to characterize it.Methods: Five specimens were collected from the margin of the El Parque stream (Tucumán-Argentina). A part was herborized and the other part was fixed in FAA. Subsequently, conventional histological techniques were used and stoma density and size of stomata and trichomes were determined. Histochemical tests were performed to detect starch (lugol) and phenolic compounds (10% ferric chloride).Key results: Anemia phyllitidis var. phyllitidis shows diarch roots and dictyostelic rhizome covered with glandular trichomes. The petiole is covered by glandular trichomes, epidermis and subepidermis composed of lignified fibers, vascular bundle with phloem surrounding xylem, two-layered pericycle surrounded by endodermis and cortical tissue with starch and phenolic compounds. Sterile pinnae have pericytic, anomocytic, and desmocytic stomata (mean size 49.8 µm × 38.7 µm); glandular trichomes; dorsoventral hypostomatic lamina, vascular bundles with pericycle and endodermis. Fertile pinnae are anatomically similar to the rachis. Silica is present in some epidermal cells of the different organs.Conclusions: The sporophyte of A. phyllitidis var. phyllitidis showed anatomical, morphological and physiological traits that reveal its adaptation to the riparian habitat where it grows. At the same time, the description of this variety is deepened and unpublished data for the genus are provided, such as the presence of stegmata in the fertile pinnae.